PENGARUH FOREST STEWARDSHIP COUNCIL (FSC) DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI MODERASI - Sebrina, Wilda (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This research aims to empirically test the Forest Stewardship Council certification and leverage on firm value moderated by firm size. FSC serves as a legitimacy and also a signal for the market regarding the responsibility of forest- raw material usage in its business. Leverage also acts as a signal for investors in managing its capital structure. This quantitative research uses a sample of 45 companies spread across the Consumer Non-Cyclicals, Basic Materials, Consumer Cyclicals, and Industrial sectors, analyzed through moderation regression analysis. The research findings indicate that FSC does not affect the company's value, leverage has a significantly positive impact on the company's value, company size does not moderate the relationship between FSC and the company's value, and does not fully moderate the relationship between leverage and the company's value.